DARI GAMEPLAY MENJADI KAJIAN KEAGAMAAN : TRANSFORMASI PRAKTIK KEAGAMAAN SEBAGAI EKSPRESI KESALEHAN GENERASI MUDA DI ROBLOX - Isna Salsabila Muthoharoh (Makkah: Journal Of Islamic Studies, 2025)
This study analyzes the transformation of religious practices on the Roblox gaming platform as a manifestation of contemporary piety among the youth. Using a qualitative netnographic approach to the Majelis Roblox Indonesia (MARIO) and Roblox Muslim Community (RMC), it explores the utilization of Roblox's technical features for religious activities through Heidi A. Campbell’s “Digital Religion” framework. Findings indicate that Roblox has evolved from an entertainment medium into an effective space for religious expression, facilitated by multi-platform strategies. These virtual practices represent the characteristics of contemporary digital religion, where digital culture shapes new religious practices while simultaneously ‘culturalizing’ new media by integrating offline religious values into digital spaces. This study concludes that technology is not merely a supplementary tool but has become deeply integrated into the daily religious structures of the younger generation as a core part of their digital identity.